Renewable energy policy status and challenges of POME-biogas industry in Malaysia - Wong, Siew Yien; Sharaai, Amir Hamzah; Mohd Kusin, Faradiella; Ismail, Mohd Mansor (School of Graduate Studies, Universiti Putra Malaysia, 2015)
Palm oil can be considered as a mainstay in the regional development and economic growth of Malaysia. It is an important raw material for local industries and as an export product. Most recently, palm oil has been referred to as a promising feedstock for the production of biofuel which could lead Malaysia towards a low carbon society. With the growing concern towards the increase of energy demand and global warming, the conversion of palm biomass to biogas for power generation has then been recognized as a feasible option in response to the mentioned problems. Nevertheless, various constraints have come in the way to slow down the biofuel production. Therefore, this paper presents an overview on the existing renewable energy (RE) policy and its current programme status, as well as to identify the challenges facing the Malaysian palm oil mill effluent (POME) and biogas industry in order to propose appropriate measures for further improvement of the programme.